A Note on Internet Resources for the Entrepreneur: A Small Firm Finance Perspective - James C. Brau (Journal of Entrepreneurial and Small Business Finance, 1996)
This article concentrates on internet resources that are available to those interested in entrepreneurial and small firm finance. Specifically, I present web pages that focus on general entrepreneurial issues and different avenues for acquiring capital. The three main areas of external financing that I include are venture capital, going public, and loans. Additionally, the advantages of using electronic mail, distribution lists, and personal web page applications are discussed and several examples presented.
Keywords: L25; G32; M13; L86; 650; Entrepreneur; Finance; Internet Resources; Small Firms